AIDS- and sexuality-related stigmas underlying the use of post-exposure prophylaxis for HIV in Brazil: findings from a multicentric study. Issue 3 (29th November 2019) - Ferraz, Dulce; Couto, Marcia Thereza; Zucchi, Eliana Miura; Calazans, Gabriela Junqueira; dos Santos, Lorruan Alves; Mathias, Augusto; Grangeiro, Alexandre
Abstract: AIDS-related stigma is a major hurdle to care and it hinders people from accessing HIV prevention methods, such as post-exposure prophylaxis. This study was designed to explore how AIDS-related stigma impacts the experience of using non-occupational post-exposure prophylaxis (nPEP) for HIV after sexual contact. Data were gathered in in-depth interviews with 59 people who voluntarily sought out nPEP in five public healthcare facilities in Brazil between 2015 and 2016. Data were analysed into three thematic categories: fear of being mistaken for a person living with HIV and AIDS (PLWHA); desire to hide particular features of one's sexual life; and experiences of stigmatising behaviour due to nPEP use. Based on the Health Stigma and Discrimination Framework, predominant manifestations of AIDS-related stigma in each category were analysed, as well as their intersections with gender- and sexuality-related stigmas. Results show that experiences of using nPEP are permeated by AIDS-related stigma, intersecting with sexuality- and gender-related stigmas. Stigma experiences are mainly perceived, anticipated and internalised; stigma practices include prejudice and stigmatising behaviours. Taking antiretrovirals (ARVs) led participants to the fear of being discriminated against as a PLWHA and having particular features of their sexual identities disclosed. Thus, hiding nPEP was strategic to protect from stigmatising behaviour. As ARV-based prevention technologies are scaled-up, interventions designed to tackle AIDS- and sexuality-related stigmas must be expanded in Brazil. Required interventions include public campaigns about nPEP, educational programmes in healthcare settings to offer adequate support to nPEP users and investments in stigma research and monitoring.